Efek Pemberian Intervensi Fisioterapi pada Kasus Cervical Root Syndrome : A Case Report - Annisa Rizky Amalia; Isnaini Herawati; Sri Isnin Kadarti (STIKES Columbia Asia Medan, 2025)
Background: Cervical Root Syndrome (CRS), Cervical Radiculopathy, or Irritating Compression Brought on by the Invertebral Discnue Can All Induce Sensory or Motor Loss. In the instance of cervical root syndrome, this study attendes to ascertain the benefits of myofacial release, free active exercise, neck calliet exercise, stretching, and transcutaneous electrical nerve stimulation (tens). Method: Patients with Cervical Root Syndrome at Dr. Hospital Sardjito Yogyakarta are the subjects of this case study. Pain, Muscle Weakness, Restricted Range of Motion, and diminished functional activity are the issues that patients face. Findings: Assessment of visual pain Analog scale (VAS) reveals that pain in the NECK region of silent pain decreases from 6 to 4 pain Decreased pressure from 7 to 5, pain decreases from 8 to 6 and in the shoulder region there is a change in pain decreases from 6 to 4 pain decreases from 7 to 6, pain movement decreases from 8 to 6. extension, lateral flexion (D), lateral flexion (s), rotation (D), rotation (s) muscle strength there is no change with the value of MMT 3+ and in the shoulder region there are changes in each movement (extension flexion, adduction, abduction, internal rotation of external rotation rotation) NECK extension-flexion movement, which changes from S: 35 ° -0-20 ° to S: 45 ° -0-25 °, and rotation movement (D)-Rotation (s), where R: 70 ° -0-60 ° to R: 80 ° -0-70 °, in the Shoulder region extension-flexion, which changes from S: 25 ° -0-80 ° 45 ° -0-130 °, and abduction-adduction movement, where f: 90 ° -0-70 ° to F: 160 ° -0-50 ° Functional activity measured by the NECK Disability Index (NDI) shows an increase from the value of 40% decreased to 38%. Conclusion.